HUBUNGAN ANTARA TAHAP PELAKSANAAN SOLAT FARDU DENGAN KONFLIK RUMAH TANGGA: KAJIAN DI UNIT RUNDINGCARA KELUARGA (URK) BAHAGIAN PERKAHWINAN DAN PEMBANGUNAN KELUARGA (BPPK), JABATAN AGAMA ISLAM WILAYAH PERSEKUTUAN (JAWI): The Relationship between the Implementation of Solat with Domestic Conflict: A Study at the Family Consultation Unit, the Marriage and Famil Development Division of the Federal Territory of Islamic Affairs Department (JAWI) - Zakaria, Nur Dalilah; Azahari, Raihanah (Jurnal Syariah, 2019)
Solat is the act of worship that manifests the meaning of total submission to Allah as a sign of faith and is a means for the believers to seek the glory in this life and the Hereafter. Allah has assigned solat as an immutable worship in every Prophetic message. This study aims to examine the relationship between the implementation of obligatory solat and domestic conflict. The respondents are married couples who have attended consultation sessions at the Family Consultation Unit, the Marriage and Family Development Division of the Federal Territory of Islamic Affairs Department (JAWI). This study also tries to identify the influence of certain factors that affect the performance of solat including educational and socio-economic factors, as well as to identify any differences in the implementation of solat based on these factors. The findings of the survey showed that there are differences in terms of the implementation of solat based on the educational background. However, the analysis found that there is no significant relationship between commitment to the performance of solat and marital conflict.